Luck and last resorts - Ruiz, Sarah Grunder (Jove, 2022)
"They have a second chance at love, but there are some rough seas ahead in the new contemporary romance from the acclaimed author of Love, Lists, and Fancy Ships Commitment-phobe Nina Lejeune lives by two rules: 1. Always have fun. 2. Don't rely on anyone but yourself. The first rule is easy; the second, she's only broken once. Ten years after fleeing home, Nina is the chief stewardess on the super yacht Serendipity, single by choice, and perfectly content with how life has turned out. But Nina's ex-coworker and old flame, Irish chef Ollie Dunne, isn't so happy with the status quo. One year after leaving yachting, he's returned as the Serendipity's chef with an ultimatum: if Nina continues to deny she's in love with him by the end of this charter season, he'll go back to Ireland for good. Nina and Ollie's shared secret from their past threatens to shipwreck not only their relationship, but the entire boat. But as their connection grows amidst chaotic guests and crew drama, could there be smooth sailing in their future?"--